Abundance and distribution of narwhals (Monodon monoceros) on the summering grounds in Greenland between 2007-2019 - Hansen, R. G.; Borchers, D. L.; Heide-Jørgensen, M. P. (Frontiers in Marine Science, 2024)
Narwhal abundance in West Greenland (WG) and East Greenland (EG) was estimated from aerial surveys conducted between 2007 and 2019 at their summer grounds. Analyses were completed using Mark Recapture Distance Sampling and Hidden Markov Line Transect Models taking account of the stochastic availability of diving whales. No statistically significant difference in abundance of narwhals could be detected for the two summer grounds (Melville Bay and Inglefield Bredning) in WG between 2007 and 2019. The distribution of narwhals in Inglefield Bredning was similar between years but in Melville Bay, area usage has decreased >80% since the first survey in 2007. Few detections of narwhals were obtained during the surveys in EG and a common detection function was fitted from combining sightings from seven surveys. Narwhals were found in small aggregations distributed between Nordostrundingen and south to and including Tasiilaq. Abundance of narwhals was estimated for the first time in the relatively unexplored Northeast Greenland (Dove Bay and a restricted coastal area of the Greenland Sea). The abundance in these two